Preliminary Memorandum on the Fourth Five Year Plan for Manipur - Planning Commission (Planning Commission, 1965)
The original outlay approved for Manipur for the Third Five Year Plan was Rs. 1,287,58 lakhs and according to the Budget figures presented in the Legislature for 1965-66,the estimated plan expenditure is Rs. 1465,85 lakhs by the end of 1965-66.
Planning Commission Government of India
Planning Commission Government of India